2001
DOI: 10.1177/0093854801028001001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Support for Police Use of Force, the Death Penalty, and Perceived Harshness of the Courts

Abstract: Logistic regression models were estimated using the 1994 General Social Survey to examine effects of race, gender, and geographical region on support for various criminal justice policies. Dependent variables included support for capital punishment, perceived harshness of courts, and support for police use of force under five conditions of escalating severity. African Americans were less likely to support capital punishment and police use of force than their counterparts. These results were enhanced when re-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 7 publications
6
54
0
8
Order By: Relevance
“…Gender was not a significant predictor in several studies that examined citizens' evaluations of the courts (Turpen & Champagne, 1978;Tyler, 2001), perceptions of criminal injustice (Henderson et al, 1997), and legitimacy and harshness of the courts (Fossati & Meeker, 1997;Halim & Stiles, 2001). Others reported a significant link between gender and perceptions of the courts (Fossati & Meeker, 1997;Hagan & Albonetti, 1982;Winkle & Wedeking, 2003).…”
Section: Gender and Citizen Perceptions Of Courtsmentioning
confidence: 96%
See 1 more Smart Citation
“…Gender was not a significant predictor in several studies that examined citizens' evaluations of the courts (Turpen & Champagne, 1978;Tyler, 2001), perceptions of criminal injustice (Henderson et al, 1997), and legitimacy and harshness of the courts (Fossati & Meeker, 1997;Halim & Stiles, 2001). Others reported a significant link between gender and perceptions of the courts (Fossati & Meeker, 1997;Hagan & Albonetti, 1982;Winkle & Wedeking, 2003).…”
Section: Gender and Citizen Perceptions Of Courtsmentioning
confidence: 96%
“…Only a small number of previous studies included gender in the analyses and the results were far from conclusive. For instance, some found that gender had a weak relationship with perceptions of criminal injustice (Halim & Stiles, 2001;Henderson et al, 1997;Turpen & Champagne, 1978), while others reported that gender shaped perceptions of the criminal courts (Fossati & Meeker, 1997;Hagan & Albonetti, 1982;Winkle & Wedeking, 2003). More research is clearly needed to clarify the connection between gender and perceptions of criminal courts.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also operationalized conflict theory to find that people of color are not only more likely to disapprove of police use of force (Thompson and Lee 2004;Halim and Stiles 2001) but are also more likely to believe that the criminal justice system is unfair (Hagan and Albonetti 1982). Therefore, people of color tend to lack confidence in the ability of the police to treat people impartially (Weitzer and Tuch 1999).…”
Section: Race Difference and Perceptions Of Police Misconductmentioning
confidence: 99%
“…With regard to gender, the majority of studies conducted in this area have found that women hold less punitive sentencing attitudes than males. Women are more likely to oppose capital punishment than males in general, and are less supportive of the death penalty for juvenile and adult offenders (Applegate, Cullen, Fisher & Vander Ven, 2000;Applegate, Wright, Dunaway, Cullen, & Wooldredge, 1993;Grasmick, Cochran, Bursik, & Kimpel, 1993;Halim & Stiles, 2001;Keil & Vito, 1991;Kelley & Braithwaite, 1990;Moon, Wright, Cullen, & Pealer, 2000;Robbers, 2006;Sandys & McGarrell, 1995;Skovron, Scott, & Cullen, 1989;Unnever & Cullen, 2005;Vogel & Vogel, 2003;Young, 1992;Zeisel & Gallup, 1989). Additionally, females tend to endorse the idea of treatment over punishment of offenders (Applegate, Cullen, & Fisher, 2002;Cullen, Clark, Cullen, & Mathers, 1985).…”
Section: Factors Impacting Sentencing Attitudesmentioning
confidence: 99%
“…Regarding race/ethnicity, past research has revealed that in general, minorities hold less punitive attitudes than non-minorities (Applegate et al, 1993(Applegate et al, , 2000Barkan & Cohn, 1994Bohm, 1999;Cochran & Chamlin, 2006;Halim & Stiles, 2001;Unnever & Cullen, 2005, 2007aYoung, 1991Young, , 1992. For example, Buckler, Davila, and Salinas (2008) found that Whites hold more punitive attitudes regarding punishment compared to African-Americans, and AfricanAmericans tend to be less supportive of the death penalty than Whites.…”
Section: Factors Impacting Sentencing Attitudesmentioning
confidence: 99%